2007
DOI: 10.1093/ejo/cjl089
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory muscle thickness, bite force, and occlusal contacts in young children with unilateral posterior crossbite

Abstract: Few investigations have evaluated the characteristics of functional and structural malocclusion in young children. Thus, the aim of this study was to assess the ultrasonographic thickness of the masseter and anterior portion of the temporalis muscles, the maximum bite force, and the number of occlusal contacts in children with normal occlusion and unilateral crossbite, in the primary and early mixed dentition. Forty-nine children (26 males and 23 females) was divided into four groups: primary-normal occlusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
21

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 50 publications
4
78
0
21
Order By: Relevance
“…When we searched for crossbite, the focus of this study, we found many studies in children with proved functional alteration, exemplified by the reduced bite force [5,[14][15][16][17][18]; however, limited evidence has been found in adults for this specific malocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we searched for crossbite, the focus of this study, we found many studies in children with proved functional alteration, exemplified by the reduced bite force [5,[14][15][16][17][18]; however, limited evidence has been found in adults for this specific malocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in children have demonstrated less electromyographic activity on the cross side during mastication [4], muscle atrophy visualized by ultrasonography (US), and decreased MBF [5].…”
Section: Introductionmentioning
confidence: 99%
“…The use of both intercanine distance between cusp tips and between cervical points is justified because the latter distance is more reliable and less susceptible to tooth inclination. But the use of ultrasound in scientific research provides reproducible and easy access to the masticatory muscles thickness, obtaining quantitative information on functional ability and determination of structural changes 17 , without the subject's exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The transducer was placed perpendicular to the muscle fiber direction, using an air-tight inert gel on the skin surface, and moved gradually to obtain optimal visualization 17 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation